Nearly isotropic Lyman-α1 radiation 2p3/2→1s1/2 following nonradiative electron capture in Xe54+ + Kr collisions at 197 MeV u−1. (14th March 2023) - Yang, Bian; Wu, Zhongwen; Yu, Deyang; Shao, Caojie; Xue, Yingli; Wang, Wei; Song, Zhangyong; Zhang, Mingwu; Liu, Junliang; Lu, Rongchun; Wu, Yehong; Ruan, Fangfang; et al.
Abstract: We measured the angular distribution of the subsequently emitted Lyman- α 1 transition of Xe 53+* ions following nonradiative electron capture in collisions of 197 MeV u −1 Xe 54+ projectiles with gaseous krypton target. The alignment of the projectile 2 p 3/2 state and the relative population of its magnetic substates were further deduced. In contrast to the available lower energy results (Yang et al 2020 Phys. Rev. A 102 042803), it is found that at 197 MeV u −1 the Lyman- α 1 radiation becomes much less anisotropic and the magnetic substates are nearly statistically populated. Moreover, the experimental findings are compared with the results of the corresponding radiative electron capture mechanism, obviously different energy dependence of the magnetic-substate population is obtained and discussed using semiclassical arguments, which help reveal the population mechanism of excited states in collisions of highly charged high- Z ions with atoms.